2015
DOI: 10.1001/jamapediatrics.2015.1148
|View full text |Cite
|
Sign up to set email alerts
|

Geographic Variation in Hospitalization for Lower Respiratory Tract Infections Across One County

Abstract: IMPORTANCE Bronchiolitis and pneumonia are leading causes of pediatric hospitalizations. Identifying geographic patterns in hospitalization rates across small geographic areas could be particularly relevant to targeted patient-level and population-level health care.OBJECTIVE To determine whether lower respiratory tract infection hospitalization rates varied geographically across a single county and whether such variability was associated with socioeconomic conditions. DESIGN, SETTING, AND PARTICIPANTS Cross-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 45 publications
2
40
0
Order By: Relevance
“…In addition, significant hotspots of bronchiolitis hospitalizations in this county were noted in high-poverty areas of the inner city. 43 The present study has some limitations. As it is an ecological study, the observed associations do not prove causality.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In addition, significant hotspots of bronchiolitis hospitalizations in this county were noted in high-poverty areas of the inner city. 43 The present study has some limitations. As it is an ecological study, the observed associations do not prove causality.…”
Section: Discussionmentioning
confidence: 81%
“…In another study performed in Ohio, USA, the population in the highest quintile of bronchiolitis hospitalization rates had significantly lower annual household income than that of lower hospitalization rate quintiles. In addition, significant hotspots of bronchiolitis hospitalizations in this county were noted in high‐poverty areas of the inner city …”
Section: Discussionmentioning
confidence: 89%
“…3 Understanding unique neighborhood risk factors and being able to utilize available neighborhood resources might help to reduce admission rates and health care costs. The need for residents to understand complex systems and navigate them with patients is at the core of the system-based practice competency domain (Fig.…”
Section: Step 1: Problem Identification and General Needs Assessmentmentioning
confidence: 99%
“…1,2 Likewise, one’s neighborhood has been shown to shape multiple health outcomes including life expectancy. 3,4 Pediatric residency training on the social determinants of health (SDH) currently focuses on understanding the effect of poverty on child health with less attention to neighborhood location and the relevant, available resources that reside within local communities. Previous curricula examining the disparities that exist across local neighborhoods have primarily taken the form of short-term windshield surveys or asset mapping.…”
mentioning
confidence: 99%
“…Adult bacteremic pneumococcal pneumonia and infant risk of developing pneumonia have both been associated with lower income and education [7]. Similarly, pneumonia hospitalization rates have been significantly associated with socioeconomic deprivation [8, 9], and geographic variation in pneumonia hospitalization has been associated with underlying socioeconomic conditions [8]. However, whether spatial variability is also linked to other demographic and environmental factors beyond socioeconomic status and education is not well described.…”
Section: Introductionmentioning
confidence: 99%